Selected legal aspects of food information in Finland - Jackowska, Anna (Przegląd Prawa Rolnego, 2025)
This article presents Finnish regulations on food information and attempts to identify those of the solutions presented that could be adopted by Polish legislators. In order to achieve this aim it examines voluntary product origin labelling, the deposit system, alcohol advertising and “GMO-free” labelling. Their analysis leads to the conclusion that Finland has introduced solutions that promote local patriotism and facilitate informed consumer choice by providing detailed information. The author believes that Finnish solutions such as the zero tolerance principle for “GMO-free” labelling and the modern deposit system could serve as good examples for Polish legislators. The introduction of similar solutions in Poland might contribute to improving consumer protection and food quality on the market.